1986
DOI: 10.1111/j.1365-2125.1986.tb05180.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous adenosine in the treatment of supraventricular tachycardia: a dose‐ranging study and interaction with dipyridamole.

Abstract: Increasing doses of adenosine were given by rapid intravenous bolus to seven patients with spontaneous supraventricular tachycardia. Adenosine restored sinus rhythm in 10 of 14 episodes of narrow complex tachycardia. In those patients in whom adenosine produced only transient ventricular slowing the underlying rhythm was atrial flutter. Transient dyspnoea occurred in all patients. In two patients taking dipyridamole the mean dose of adenosine which produced an electrophysiologic effect (restoration of sinus rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…ATP was shown to evoke transient tachycardia at low doses and to induce AV block at high doses [659,660]. Later, adenosine was also found to be effective in the acute termination of PSVT [661,662] and was used effectively in children [663][664][665][666]. The mechanism of terminating the arrhythmias by either adenosine or ATP is the induction of transient complete AV nodal conduction block.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…ATP was shown to evoke transient tachycardia at low doses and to induce AV block at high doses [659,660]. Later, adenosine was also found to be effective in the acute termination of PSVT [661,662] and was used effectively in children [663][664][665][666]. The mechanism of terminating the arrhythmias by either adenosine or ATP is the induction of transient complete AV nodal conduction block.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…During our initial evaluation of adenosine for treatment of this arrhythmia in man (Watt et al, 1985) we observed that adenosine produced hyperpnoea at about the time that it exerted its cardiac electrophysiological effects (unpublished observations). In a subsequent study of the negative chronotropic effects of adenosine on the hearts of normal volunteers we observed that adenosine was a powerful but short-lived subjective respiratory stimulant (unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…Although adenosine may have intrinsic anticonvulsant activity,9,15,69, it does not cross the blood-brain barrier, 71 but analogues of adenosine capable of entering the brain might be potentially useful. Whilst intravenous bolus doses of adenosine have been used to terminate paroxysmal tachycardias in patients, 11,12,14,27,72,73 there are no data on the effect of adenosine in theophylline-induced tachycardias. Bolus doses of adenosine are now used as an antiarrhythmic as they produce a transiently high local concentration of adenosine at the sinoatrial node.29 Thus, a single bolus dose of adenosine might be sufficient to abort an episode of supraventricular tachycardia due to theophylline.…”
Section: Discussionmentioning
confidence: 99%